Kekebun: portable solar hydroponics for sustainable home farming - Abdul Aziz, Mohd Nasiruddin; Mohamad Faizar, Muhammad Kamil; Saari, Nur Syafinaz; Faizol, Faiz Hilmi; Abdul Halim, Muhammad Solehin (2025)
Kekebun is an innovative and portable hydroponic system that combines solar power and automated watering to support sustainable home farming. It is designed for urban users who face space and access limitations to electricity, allowing them to grow fresh vegetables efficiently without relying on traditional power sources. The system features a vertical planting structure to maximize growing capacity, a solar-powered pump for automatic nutrient circulation, and a wheeled frame for easy mobility and placement. Unlike conventional hydroponic systems, Kekebun offers energy independence, low maintenance, and user-friendly operation, making it suitable for homes, educational institutions, and small community projects. Since its launch, Kekebun has sold more than 300 units in both local and international markets, demonstrating strong commercial potential and market acceptance. Buyers have consistently highlighted its practicality, cost efficiency, and environmental benefits. In addition to its commercial success, Kekebun has played an active role in promoting sustainability through collaborations with schools, government agencies, universities, and local communities. These partnerships support knowledge sharing and environmental education, further expanding the impact of the product beyond home farming. Kekebun makes meaningful contributions to global efforts in clean energy, responsible consumption, and urban food security, positioning it as a scalable and market-ready solution for sustainable urban agriculture.